Identifying α-KG-dependent prognostic signature for lower-grade glioma based on transcriptome profiles - Zhang, Tan; Yuan, Liqun; Sheng, Minfeng; Chen, Yanming; Wang, Ji; Lan, Qing (Frontiers in Oncology, 2022)
The inhibition of alpha-ketoglutarate (α-KG)-dependent dioxygenases is thought to contribute to isocitrate dehydrogenase (IDH) mutation-derived malignancy. Herein, we aim to thoroughly investigate the expression pattern and prognostic significance of genes encoding α-KG dependent enzymes for lower grade glioma (LGG) patients. In this retrospective study, a total of 775 LGG patients were enrolled. The generalized linear model, least absolute shrinkage and selection operator Cox regression and nomogram were applied to identify the enzyme-based signature. Gene set enrichment analysis and gene ontology were utilized to explore the potential molecular alterations underlying risky patients. By comprehensively analyzing mRNA data, we observed that 41 genes were differentially expressed between IDHMUT and IDHWT LGG patients. A 10-genes comprised risk signature, which could divide samples into high- and low- risk groups of distinct prognosis, was developed and independently validated. This enzyme-based signature was indicative of a more malignant phenotype. The nomogram model integrated with the risk signature, molecular biomarkers, and clinicopathological characteristics achieved a better predictive effect, which well demonstrated the incremental value of the α-KG-dependent signature. Our study demonstrates that the α-KG-dependent enzyme-encoding genes were differentially expressed relevant to IDH phenotype and may serve as a promising indicator for clinical outcomes of LGG patients.